Jobs as Dam Sites - Akerlof, George A. (Review of Economic Studies, 1981)
Journal Article Jobs as Dam Sites Get access George A. Akerlof George A. Akerlof London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 1, January 1981, Pages 37–49, https://doi.org/10.2307/2297119 Published: 01 January 1981 Article history Received: 01 July 1978 Accepted: 01 August 1980 Published: 01 January 1981